2017
DOI: 10.1021/acsomega.7b00192
|View full text |Cite
|
Sign up to set email alerts
|

Auric Chloride Induced Micellization on Fractal Patterned Dicationic Amphiphiles and Stabilization of Gold Nanoparticles

Abstract: The present article reports the development of sunlight-mediated rapid synthesis of bile acid derived dicationic amphiphiles, namely, dicationic cysteamine-conjugated cholic acid (DCaC), dicationic cysteamine-conjugated deoxycholic acid (DCaDC), and dicationic cysteamine-conjugated lithocholic acid (DCaLC) by adopting thiol–yne click chemistry approach. The auric chloride (AuHCl 4 ) induced micellization of amphiphiles from fractal pattern to chainlike aggregates was examined by critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…There have been interesting experiments in which cholic, deoxycholic, and lithocholic acids were modified with cysteamine and used for the manufacturing of Au NP suspensions with enhanced stability. [34] Ag and Au NPs were also prepared [35] using phenylalanineconjugated cholic acid for application in colorimetric sensors. It was found that ─OH and NH─C═O groups of phenylalanineconjugated cholic acid were involved in the reduction of ions in the precursor solutions, whereas other hydrophilic and hydrophobic groups facilitated particle dispersion.…”
Section: Hauclmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been interesting experiments in which cholic, deoxycholic, and lithocholic acids were modified with cysteamine and used for the manufacturing of Au NP suspensions with enhanced stability. [34] Ag and Au NPs were also prepared [35] using phenylalanineconjugated cholic acid for application in colorimetric sensors. It was found that ─OH and NH─C═O groups of phenylalanineconjugated cholic acid were involved in the reduction of ions in the precursor solutions, whereas other hydrophilic and hydrophobic groups facilitated particle dispersion.…”
Section: Hauclmentioning
confidence: 99%
“…There have been interesting experiments in which cholic, deoxycholic, and lithocholic acids were modified with cysteamine and used for the manufacturing of Au NP suspensions with enhanced stability. [ 34 ]…”
Section: Synthesis and Dispersion Of Inorganic Npsmentioning
confidence: 99%
“…[31] Besides they reported bile acid derived facially amphiphilic thiols stabilized Ag and Au NPs. [32] Clarke et al demonstrated in-vitro antibacterial activity of unconjugated and conjugated bile salts on Staphylococcus aureus. [33] Camilleri et al reported antimicrobial activity of new bile acid-based gemini surfactants where it and they showed increased antibacterial activity as increase in the number of primary amino groups.…”
Section: Introductionmentioning
confidence: 99%